2004
DOI: 10.1016/j.bbapap.2004.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the allergenic soybean Kunitz trypsin inhibitor

Abstract: The soybean Kunitz trypsin inhibitor (SKTI) is a 21.5 kDa allergenic protein that belongs to the family of all antiparallel h-sheet proteins that are highly resistant to thermal and chemical denaturation. Spectroscopic and biochemical techniques such as circular dichroism (CD), ANS fluorescence and proteolysis were used to study its molecular structure under denaturing conditions such as acid and heat to which these allergens are commonly exposed during food processing. Reduction of native SKTI leads to its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…Unlike most Soybean Kunitz-type inhibitors which exhibit a high degree of structural and functional stabilities at a range of temperatures and pH (Sweet et al, 1974;Onesti et al, 1991;Roychaudhuri et al, 2003Roychaudhuri et al, , 2004Azarkan et al, 2006), MKMLP showed unusual stability properties. It possesses a compact structure which is retained at high temperature but functional stability is lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most Soybean Kunitz-type inhibitors which exhibit a high degree of structural and functional stabilities at a range of temperatures and pH (Sweet et al, 1974;Onesti et al, 1991;Roychaudhuri et al, 2003Roychaudhuri et al, , 2004Azarkan et al, 2006), MKMLP showed unusual stability properties. It possesses a compact structure which is retained at high temperature but functional stability is lost.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Kunitz soybean trypsin inhibitors are proteins with molecular mass of about 20 kDa. The stability studies have shown that most Kunitztype inhibitors are highly stable over a broad range of pH and temperature with a remarkably resistance to proteolytic degradation (Sweet et al, 1974;Onesti et al, 1991;Roychaudhuri et al, 2003Roychaudhuri et al, , 2004Azarkan et al, 2006). It has been reported that a Bowman-Birk inhibitor is involved in the tolerance of salt stress in wheat (Shan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean KTI is classifi ed in the family of antiparallel β -sheet proteins that are highly resistant to chemical and thermal denaturation [73] . Moroz and Yang [74] demonstrated that the serum of a patient with an occupational respiratory disorder had IgE antibodies specifi c for soybean KTI (21 kDa).…”
Section: Kunitz Trypsin Inhibitor (Kti)mentioning
confidence: 99%
“…Interestingly, because of the infl uence of anions on A state stability, not all acids are capable of quantitatively precipitating such proteins (58) . Note also that some structured proteins adopt nonsticky A states and thus remain in solution (55) . Finally, some ordered proteins might be exceptionally stable and simply remain folded and soluble even at extremely low pH (57,61) .…”
Section: Basic Principles Of the Approachmentioning
confidence: 99%